gamma-Al2O3/triflic acid as cooperative catalysts for the tandem Michael addition/carbocyclization: an easy access to 2-substituted pyrrolo[2,1-a]isoquinolines and 3-substituted pyrrolidine-2,5-diones - Rao, Ramana Sreenivasa; Sahani, Anita; Ali, Sheikh Haider; Pradhan, Sumanta; Ramanathan, Chinnasamy Ramaraj (Journal of Heterocyclic Chemistry, 2021)
A tandem Michael addition/carbocyclization of 3,4-dimethoxyphenethyl maleimide with carbon and sulfur nucleophiles is accomplished via a relay catalysis using gamma-Al2O3/TfOH binary system. The X-ray Photoelectron Spectroscopy (XPS) analysis of binary system indicates the presence of AlF3, AlO(OH) species(.) This approach provides an easy access to 2-aryl or 2-thio aryl pyrrolo[2,1-a]isoquinolines in good yields in a tandem fashion. With suitable ratio of gamma-Al2O3/TfOH binary system, the Michael addition of N/C/S nucleophiles to N-benzyl maleimide is also achieved. A key to the success of these reactions would be the generation of AlF3, AlO(OH) species from gamma-Al2O3 and TfOH, which might have delineated the disadvantageous background reactions usually displayed by a strong Bronsted acid such as TfOH.
Keywords: 1-a]isoquinolines; 3-substituted pyrrolidine-2; 5-diones; carbocyclization; gamma-Al2O3/TfOH binary system; Michael addition; pyrrolo[2